Transforming Teaching and Learning - Hidayatullah Hidayatullah; Mustofa Kamil; Suherman Suherman (STAI Miftahul Ula Nganjuk, 2023)
This research discusses strategies to enhance teacher competencies through workshop activities using Zoom media and a Learning Management System (LMS)-based platform in Lebak Regency. Workshops are an effective method for improving teacher competencies, and with the development of digital technology, the use of Zoom media and LMS can provide efficient and flexible solutions. Zoom media allows direct interaction among workshop participants, even when they are in different locations. Features such as group chat, video capabilities, and screen sharing facilitate discussions and collaboration among participants. Meanwhile, the use of an LMS platform enables structured access to learning materials, assignments, and online exercises. Teachers can access the materials anytime and anywhere, allowing them to learn according to their needs and available time. The methodology used in this research is literature review.